PERTANGGUNGJAWABAN PIDANA KORPORASI PT FREEPORT INDONESIA ATAS PENCEMARAN SUNGAI AGHAWAGON DAN OTOMONA AKIBAT LIMBAH TAILING: KAJIAN PENERAPAN DOKTRIN STRICT LIABILITY - Surya Insani Kamil (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
This study examines the corporate criminal liability of PT Freeport Indonesia for the pollution of the Aghawagon and Otomona Rivers due to the discharge of mine tailings, with a focus on applying the strict liability doctrine under Article 88 of Law Number 32 of 2009 on Environmental Protection and Management. The research employs a normative-empirical legal approach, analyzing environmental data such as water quality, sedimentation, heavy metals (Cu, Pb, Hg), and the ecological and social impacts on indigenous communities in Papua. The findings reveal that Freeport’s tailings activities have caused severe environmental degradation, exceeding legal thresholds and disrupting local livelihoods. Legally, these actions fulfill the elements of environmental criminal offenses and justify imposing criminal liability on the corporation and its executives, based on Article 116 of the Environmental Law and Supreme Court Regulation No. 13 of 2016. The strict liability doctrine is applicable due to the involvement of hazardous waste and serious threats to the environment, without requiring proof of fault. However, enforcement is hindered by structural, technical, and political challenges, including conflicts of interest arising from government ownership in the company. This study recommends the establishment of environmental guarantee funds, improved data transparency, and strengthened coordination among enforcement agencies. The research contributes to the advancement of environmental criminal law in Indonesia and provides a critical precedent for holding mining corporations accountable.